1997
DOI: 10.1074/jbc.272.40.25326
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Reduces Tau Phosphorylation by Inhibition of Glycogen Synthase Kinase-3

Abstract: Lithium is one of the most widely used drugs for treating bipolar (manic-depressive) disorder. Despite its efficacy, the molecular mechanism underlying its action has not been elucidated. One recent study has proposed that lithium inhibits glycogen synthase kinase-3 and thereby affects multiple cellular functions. Because glycogen synthase kinase-3 regulates the phosphorylation of tau (microtubule-binding protein that forms paired helical filaments in neurons of the Alzheimer's disease brain), we hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
287
1
8

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(315 citation statements)
references
References 62 publications
(59 reference statements)
15
287
1
8
Order By: Relevance
“…118 Although many of the studies have utilized lithium concentrations in excess of those utilized therapeutically, the available data suggest that lithium, at concentrations of ෂ1 mM does, indeed, reduce tau phosphorylation. 118,[123][124][125] Overall, the data suggest that in addition to bcl-2 upregulation, inhibition of GSK-3␤ by lithium may also afford protection against the cell death induced by various stimuli. 126 In view of the important role of GSK-3␤ in cell survival, a study was undertaken to determine if other mood stabilizers also regulate GSK3␤.…”
Section: Inhibition Of Glycogen Synthase Kinase 3␤ (Gsk-3␤) May Also mentioning
confidence: 93%
“…118 Although many of the studies have utilized lithium concentrations in excess of those utilized therapeutically, the available data suggest that lithium, at concentrations of ෂ1 mM does, indeed, reduce tau phosphorylation. 118,[123][124][125] Overall, the data suggest that in addition to bcl-2 upregulation, inhibition of GSK-3␤ by lithium may also afford protection against the cell death induced by various stimuli. 126 In view of the important role of GSK-3␤ in cell survival, a study was undertaken to determine if other mood stabilizers also regulate GSK3␤.…”
Section: Inhibition Of Glycogen Synthase Kinase 3␤ (Gsk-3␤) May Also mentioning
confidence: 93%
“…Lithium is useful in this regard, because it is a selective inhibitor of GSK3␤ (44, 45), a finding substantiated by an examination of 24 kinases, which showed that GSK3␤, and the closely related GSK3␣, to be the only kinases substantially inhibited by lithium (46). Extensive studies have clearly documented that several of lithium's prominent effects, such as inhibition of the phosphorylation of the microtubule-associated protein tau, increased levels of ␤-catenin, and protection from GSK3␤-facilitated apoptosis, are directly dependent on lithium's inhibition of GSK3␤ (24,(47)(48)(49); reviewed in Refs. 21 and 50).…”
mentioning
confidence: 93%
“…60 In addition, GSK-mediated phosphorylation of MAP-B and tau proteins regulate microtubule assembly and stabilization at synapses. 57,[61][62][63] Clinical studies have demonstrated that specific GSK-3 inhibitors mimic the therapeutic action of mood stabilizers and might therefore be plausible drugs in treating bipolar patients. 64 Crosstalk between PKC and GSK-3b signaling pathways Certain PKC isoforms have been shown to phosphorylate and inactivate GSK-3b in vitro.…”
Section: Lithium and Wnt Signaling Pathwaymentioning
confidence: 99%